(untitled) (Research, Society and Development, 2020)
This work aims to propose some reflections and considerations about Afro-Brazilian culture in the educational environment, as well as the importance of African orality in this context. We will study the contribution left by Ancient Africa passed to future generations from the word, legacy of preservation and dissemination of culture. This study is theoretical with a qualitative approach where we delve into the speeches of authors who have studied the African, Afro-Brazilian theme and aspects of oral tradition in Ancient Africa. The National Curriculum Guidelines for ethnic-racial issues (2004), as well as Laws 9.394 / 1996, 10.639 / 03 and 11.645 / 2008 formed our field of study in public policies that guarantee the inclusion of the theme in the school curriculum. We intend to collaborate so that the African, Afro-Brazilian and indigenous themes are a path of manifest, struggle, valorization and cultural reparation for educational equity.